Psychological well-being among US adults with arthritis and the unmet need for mental health care - Straub LE (Dove Medical Press, 2017)
Laura E Straub,1,2 Miriam G Cisternas3 1Emory University, Atlanta, GA, 2Immune Tolerance Network, San Francisco, CA, 3MGC Data Services, Carlsbad, CA, USA Purpose: Mental health conditions can increase the risk of disability among adults with arthritis. The objective of this analysis was to compare the prevalence of serious psychological distress (SPD), depression, and anxiety among US adults with arthritis vs. those without; characterize adults with arthritis with and without SPD; and determine correlates of seeing a mental health professional during the year for adults with arthritis and SPD.Materials and methods: Cross-sectional analysis of adults in the 2011–2013 National Health Interview Survey.Results: Higher proportions of adults with arthritis had SPD (6.8% vs. 2.4%), depression (19.4% vs. 7.3%), and anxiety (29.3% vs. 16.3%) compared to those without. Of the estimated 3.5 million adults with arthritis and SPD, only 39% saw a mental health professional during the year. Adjusted analyses identified the following statistically significant relationships: those who were older (45–64 and ≥65 [vs.18–44], prevalence ratio [PR]=0.8 and 0.4, respectively), less educated (PR=0.5 and 0.7 for high school or less vs. college degree, respectively), and without health insurance coverage (vs. any private, PR=0.7), were less likely to see a mental health professional, whereas the disabled or unemployed (vs. employed, PR=1.6 and 1.5, respectively), and those unable to afford mental health care throughout the year (PR=1.3) were more likely.Conclusion: The high prevalence of SPD, anxiety, and depression in adults with arthritis suggests the need for increased mental health screening, with subsequent referral to mental health professionals or other treatment programs, in that population. Keywords: serious psychological distress, anxiety, depression, access to mental health care, rheumatoid arthritis